Analyzing and Interpreting Eye Movements in C++ : Using Holistic Models of Image Perception - Hauser, Florian; Grabinger, Lisa; Ezer, Timur; Mottok, Jürgen H.; Gruber, Hans (United States, 2025)
This study uses holistic models of image perception originating from radiology and psychology to analyze and interpret eye movements during code reviews in the C++ programming language. The study design is based on former experiments, but is supplemented by approaches from expertise research. The study utilizes a sample of 34 subjects whose eye movements are recorded by a Tobii Pro Spectrum 600 Hz. The results show that the holistic models of image perception are suitable for application to source code. In addition, it can be observed that the code reviews are conducted in phases, which are characterized by certain strategies (e.g. scan, error detection,...). Furthermore, experience-related differences can be detected between experts and novices, which emphasize that experts use elaborate strategies and have a comparatively better ability to collect and process information from source code.
ETRA '24: Proceedings of the 2024 Symposium on Eye Tracking Research and Applications